Restauro das cúpulas do Museu Nacional de Belas Artes no Rio de Janeiro - Trevisan, R. (Revista ALCONPAT, 2014)
The current National Museum of Fine Arts was designed by Los Rios Morales to host National School of Fine Arts. It was built in 1908. It is located in Cinelandia, city center of Rio de Janeiro. The building has undergone several operations to adapt to the physical space inside the Museum. In 2005 we carried out the restoration project of the side domes, using modern technology, focusing on the durability of services to prevent further interventions in short time. The conditions existing in the domes caused irreversible damage to the original construction technique and were instrumental in the restoration actions proposed. This article aims to present the methodology for carrying out the work designed. The project lasted a year with the cooperation of multidisciplinary specialist corrosion, structural engineer, historians and architects specializing in Restoration. Keywords: Cultural Heritage; Restoration; National Museum of Fine Arts.